2019
DOI: 10.1016/j.idcr.2019.e00610
|View full text |Cite
|
Sign up to set email alerts
|

A case of recurrent Corynebacterium jeikeium endocarditis: Unanswered questions for the treatment of chronic endovascular infections

Abstract: Highlights Many factors confer increased risk of recurrent endocarditis. Often many of these factors co-exist in the same host. There is always the risk of residual infected endocardial tissue despite repeated debridement. The traditional 4–6 week parenteral course in endocarditis accounts for bacterial tolerance and antimicrobial resistance. The decision on antimicrobial therapy and duration are supported by evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Our study confirms specialized literature data [6,14,15,22,27]. The antibiotics that we tested belong to nine different classes and they are the most commonly used treatment options for Corynebacterium spp.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our study confirms specialized literature data [6,14,15,22,27]. The antibiotics that we tested belong to nine different classes and they are the most commonly used treatment options for Corynebacterium spp.…”
Section: Discussionsupporting
confidence: 89%
“…urealyticum has been associated with acute or chronic infections of the urinary tract, urolithiasis, kidney stones and ureteral stenosis [10,11]. Although considered a microorganism involved in the pathology of the urinary tract, C. urealyticum has been isolated from blood culture, endocarditis, pericarditis, osteomyelitis, wounds, and soft tissue infections [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 4 Persistence of C. jeikeium IE has been described and often requires multiple courses of vancomycin and recurrent heart valve replacements. 14 The patient in the case described had successful clearance of C. jeikeium following an aortic valve replacement combined with 6 weeks of antibiotic therapy with vancomycin.…”
Section: Discussionmentioning
confidence: 94%
“…However, the dormant forms of C. jeikeium used in the study that were produced as a result of the acidification of the environment proved to be resistant to both rifampicin and vancomycin (Figures 4B,C). Researchers previously demonstrated that, in some cases, vancomycin may be ineffective in the treatment of C. jeikeium bacteremia and endocarditis and disease recurrence occurred despite providing an extended course of antimicrobial therapy (Vanbosterhaut et al, 1989;Clarke et al, 2019). Wang et al (2001) "retrospectively reviewed 53 cases of C. jeikeium bacteremia in bone marrow transplant recipients who had a Hickman catheter without signs of local catheter site infection.…”
Section: Discussionmentioning
confidence: 99%